Penyuluhan Metode Pengelolaan Sampah Rumah Tangga di Desa Rowo, Kecamatan Mirit, Kabupaten Kebumen - Ari Sulistianto; Taryono Taryono (Jurnal Pusat Inovasi Masyarakat (PIM), 2021)
Garbage is a human daily or natural process that is solid or semi-dense in the form of organic or inorganic substances that can be decomposed or unable to decompose that are considered useless and discarded into the environment. The increase in population and changes in people's consumption patterns are the causes of the increase in household waste production. The lack of public awareness, the absence of facilities and waste management causes people to throw indiscriminately into residential neighborhoods, namely sewers, rivers, or burning them around the house. This activity is carried out to provide public education on waste management in several stages, namely field surveys, social mapping, counseling, and evaluation. Counseling is done by method of lectures, discussions, and demos. Material submitted about the types of garbage and its dangers, the introduction of the concept of TPS3R, and demos on garbage sorting. Counseling has changed people's perceptions of garbage. People become more understanding and aware to manage household waste. Finally, the community can conduct garbage collection, sorting, transporting, and weighing activities properly, proven in Dukuh Rowo Pasar successfully conducting transportation and weighing of garbage independently. The effort is the first step of the method in TPS3R. The distribution of bins is one way to reduce the indiscriminate garbage disposal activities carried out by the community. It takes community cooperation to deal with this issue. The village government should allocate budgets for the procurement of waste management facilities and infrastructure, such as trash cans, transportation of garbage transporters, and the construction of landfills (landfills). In addition, waste management education to the community also needs to be improved. Keywords: household, waste, integrated waste management, reuse, reduce, recycle